ANALISIS LAPORAN KEUANGAN DALAM MENILAI KINERJA KEUANGAN PERUSAHAAN PT HAWAII WISATA - Natasya, Nadila; Riki (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to determine the financial performance of the company PT. Hawai Wisata as seen from the Current Ratio, Debt to Asset Ratio, Debt to Quality Ratio, Fixed Asset Turnover, Gross Profit Margin, Operating Profit, and Nett Profit Margin. The type of research used is quantitative research. The data used is the financial report data of PT. Wisata Hawaii for the period 2020-2024. The analysis technique used is a quantitative technique where the analysis uses data in the form of numbers as analysis and determines the level of company performance. The results of the analysis carried out can be seen The results of the analysis show that the company's financial performance is generally in the good category. The liquidity ratio measured through the Current Ratio shows a figure of 149.6%, indicating the company's good ability to meet short-term obligations. In the solvency ratio, the Debt to Asset Ratio shows that the capital structure is more dominantly financed by equity, so that the financial risk is low, although it is below the industry standard. The Debt to Equity Ratio also shows a consistent downward trend, indicating a decrease in debt levels and strengthening of the financial position. However, in the activity ratio, Fixed Asset Turnover is considered less than good because it is below the industry average, reflecting the less than optimal use of fixed assets. Meanwhile, the profitability ratio consisting of Gross Profit Margin, Operating Profit Margin, and Net Profit Margin are all in the good category with achievements above the standard of 25%, indicating the company's ability to generate strong profits. Overall, PT. Hawaii Wisata shows a fairly solid financial performance with several aspects that need to be improved, especially in the efficiency of fixed asset use.